Analisis Pengukuran Kualitas Produk Terhadap Aplikasi Shopee Menggunakan Metode Kuantitatif - Omar Da’i Fananda; Tata Sutabri (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
This study aims to analyze the effect of product quality on purchasing decisions on the Shopee application. With the increasing use of e-commerce platforms, understanding the factors that influence consumer satisfaction and decisions is very important. The method used in this study is a quantitative approach with a descriptive design. The study population consisted of Shopee users who had made purchases, with a sample of 300 respondents taken through a purposive sampling technique. Data were collected using a questionnaire consisting of questions about product quality, reviews, prices, and purchasing decisions. Data analysis was carried out using multiple regression to test the relationship between independent and dependent variables. The results showed that product quality had a positive and significant effect on purchasing decisions, with a T-statistics value of 6.154. In addition, the promotion variable also contributed significantly to purchasing decisions. These findings indicate that improving product quality can increase consumer purchasing interest and purchasing decisions on Shopee. This study suggests that Shopee focus on improving product quality and promotional strategies to attract more customers and increase user satisfaction.